Tissue-specific expression of Arabidopsis NPR1 gene in rice for sheath blight resistance without compromising phenotypic cost. (September 2016) - Molla, Kutubuddin Ali; Karmakar, Subhasis; Chanda, Palas Kumar; Sarkar, Sailendra Nath; Datta, Swapan Kumar; Datta, Karabi
Highlights: AtNPR1 expression in rice causes enhancement in tolerance to sheath blight disease. Green tissue-specific expression does not cause any phenotypic cost in transgenic plants. AtNPR1 gene induce SAR pathway by up-regulating the expression of pathogenesis related genes. Abstract: Rice sheath blight disease, caused by the fungus Rhizoctonia solani, is considered the second most important disease of rice after blast. NPR1 (non expressor of PR1 ) is the central regulator of systemic acquired resistance (SAR) conferring broad spectrum resistance to various pathogens. Previous reports have indicated that constitutive expression of the Arabidopsis thaliana NPR1 ( AtNPR1 ) gene results in disease resistance in rice but has a negative impact on growth and agronomic traits. Here, we report that green tissue-specific expression of AtNPR1 in rice confers resistance to the sheath blight pathogen, with no concomitant abnormalities in plant growth and yield parameters. Elevated levels of NPR1 activated the defence pathway in the transgenic plants by inducing expression of endogenous genes such as PR1b, RC24, and PR10A . Enhanced sheath blight resistance of the transgenic plants was evaluated using three different bioassay systems. A partially isolated toxin from R. solani was used in the bioassays to measure the resistance level. Studies of the phenotype and yield showed that the transgenic plants did not exhibit any kind of phenotypic imbalances. Our results demonstrate that green tissue-specific expression of AtNPR1 is an effective strategy for controlling the sheath blight pathogen. The present work in rice can be extended to other crop plants severely damaged by the pathogen.